2013
DOI: 10.1103/physreva.88.023803
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic quantum metrology with strongly correlated quantum optical systems

Abstract: We show that the quasi-adiabatic evolution of a system governed by the Dicke Hamiltonian can be described in terms of a self-induced quantum many-body metrological protocol. This effect relies on the sensitivity of the ground state to a small symmetry-breaking perturbation at the quantum phase transition, that leads to the collapse of the wavefunciton into one of two possible ground states. The scaling of the final state properties with the number of atoms and with the intensity of the symmetry breaking field,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
(66 reference statements)
1
44
0
Order By: Relevance
“…The Dicke Hamiltonian exhibits a quantum phasetransition at B c = g 2 0 /|δ| in the thermodynamic limit, i.e. N → ∞, [39][40][41], separating the normal (B > B c ) and superradiant (B < B c ) phases. The Hamiltonian remains unchanged under the simultaneous transforma-tionsŜ z → −Ŝ z ,Ŝ y → −Ŝ y andâ → −â.…”
Section: Fig 1 Implementation and Dynamical Protocol (A) Thementioning
confidence: 99%
“…The Dicke Hamiltonian exhibits a quantum phasetransition at B c = g 2 0 /|δ| in the thermodynamic limit, i.e. N → ∞, [39][40][41], separating the normal (B > B c ) and superradiant (B < B c ) phases. The Hamiltonian remains unchanged under the simultaneous transforma-tionsŜ z → −Ŝ z ,Ŝ y → −Ŝ y andâ → −â.…”
Section: Fig 1 Implementation and Dynamical Protocol (A) Thementioning
confidence: 99%
“…Therefore, a question naturally arises: what sensitivity can be achieved using interacting systems close to a quantum-critical point? In the last few years, this question has attracted growing interest and it has been addressed by different methods [3][4][5][6][7][8][9]. These studies may be roughly divided in two classes.The first approach, which we will call the "dynamical" paradigm [5,7], focus on the time evolution induced by a Hamiltonian close to a critical point.…”
mentioning
confidence: 99%
“…The model introduced in (6) may be implemented with single qubit photon laser using single atoms [57] or superconducting qubits [58][59][60]. The phononic excitations in ion traps can also play the role of the bosonic field [61,62], in which case this systems allows the precise measurement of ultraweak forces resonant with the trapping frequency [14,[63][64][65][66]. A possible implementation of our model with trapped ions may be carried out by extending the implementation sketched in [14], in which it was shown that local sources of error such as heating or dephasing only result in a renormalization of the parameters.…”
Section: Discussionmentioning
confidence: 99%